Characterization, Thermal And Mechanical Properties Of Tropical Plant Fibres - Mohamed, Fibres Siti Alwani (2013)
The work deals with systematic evaluation of chemical, morphological, anatomical, thermal and mechanical properties of tropical plant fibres. The TAPPI test standard and Fourier transform infrared (FT-IR) spectroscopy were used to study the chemical composition and spectroscopic properties of plant fibre. The crystallinity was determined using X-ray diffraction (XRD). Light microscopy (LM) and transmission electron microscopy (TEM) were used to observe the morphology and cell wall structure of the fibre. Lignin distribution across cell wall layers was analyzed using scanning electron microscopy coupled with x-ray energy dispersive (SEM-EDX) and Raman spectroscopy. In addition, thermogravimetry analysis (TGA) was used to investigate thermal stability of the fibres. Meanwhile, miniature tensile tester also was used to measure the mechanical properties of fibres. Four different types of plant fibre were chosen which include coconut (COIR), banana pseudo-stem (BPS), pineapple leaf (PALF) and sugarcane bagasse (SCB) fibres for the study. Moisture content in all types of plant fibre studied was in the range between 6-9%. Cellulose content was highest in PALF (70%) while lignin was highest in COIR (28%). Meanwhile, SCB consists of the highest hemicelluloses content (10%) compared to other fibres and ash content was the highest in BPS (2.2%). Crystallinity was calculated by to peak height and deconvulated peak method. However, the results were completely different for these two methods. COIR showed the highest crystallinity (52.0%) by peak height method, whereas it was the highest in PALF (68.3%) when calculated by peak deconvulated method.